Studie tramvajové trati mezi ulicí Vídeňskou a novým hlavním nádražím v Brně - Michal, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Bakalářská práce pojednává o návrhu vedení tramvajové tratě v Brně mezi nově připravovaným Hlavním nádražím a ulicí Vídeňskou. Návrh byl zpracován variantně podle různých požadavků na obslužnost a průjezdnost územím. Jedna z navržených variant byla vybrána a prověřena podrobněji. V práci se nachází i porovnání variant vzhledem k návrhu a požadavkům na návrh.

The bachelor‘s thesis disscuses about designing tram railway in Brno between new prepared Main train station and Videňska street. The design was made in variants according to different needs for accessibility and drive through the area. One of designed variants was chosen and inspected more in detail. There is included comparsion between variants according to design and needs for designing.
Study of the New Tram Track between Videnska Street and New Main Station in Brno
Keywords: Tramvajová trať; Trasa; Varianty; Urbanismus; Tramvajový svršek; Využití území; Studie; Tram railway; Path; Variants; Urbanism; Tram superstructure; Use of area; Study